Resource efficiency and the imagined public: Insights from cultural theory. (September 2015) - Sharp, Liz; Macrorie, Rachel; Turner, Alan
Highlights: A novel framework for assessing and developing resource governance is presented. It adopts the concept of imagined publics applied using a cultural theory analysis. It is used to examine three consecutive resource efficiency initiatives in the UK. The framework's benefits, limitations and governance implications are discussed. Abstract: Resource efficiency initiatives seek to moderate how water and energy are used at a domestic level. They can address local and regional issues of resource supply while simultaneously reducing carbon emissions and water in-security, hence enabling both mitigation of and adaptation to climate change. Although they form an increasingly important part of our resource governance landscape, these interventions have received relatively little academic scrutiny to date. Utilising the concept of the 'imagined public' as a lens through which to apply an interpretive version of Douglas' cultural theory, this paper presents a novel conceptual framework to analyse the governance of such initiatives. The framework distinguishes between interventions based on assumptions about potential householder participants, 'the imagined public', which are reflected in the initiatives' design and implementation. The framework is applied to compare three initiatives located in the increasingly populous, but water-scarce, county of Kent (south-east England). The analysis reveals whether and how institutional objectives are met; it also describes the interventions' environmental and socio-political contributions, and uncovers how learning occurs between initiatives. This research suggests that whilst the target interventions differed in their assumptions, design and implementation, they all made a small contribution to more sustainable resource governance. Fundamentally, the initiatives' impact on resource consumption was limited due to a shared techno-rational approach and a narrow framing of their household participants. Moreover, while all three initiatives demonstrated aspects of cumulative institutional learning, the closer involvement of resource providers and a modified funding framework are suggested as a means to engender the transformative change required for achieving greater resource efficiency. The paper concludes that the proposed conceptual framework provides a useful means to analyse, map, and enhance resource efficiency initiatives. Further, it is argued that the framework also has wider application in addressing broader environmental and social governance challenges.